2006
DOI: 10.1176/appi.ajp.163.2.316
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Brain Chemistry in Children and Adolescents With Attention Deficit Hyperactivity Disorder With and Without Comorbid Bipolar Disorder: A Proton Magnetic Resonance Spectroscopy Study

Abstract: Objective-The authors' goal was to investigate phosphatidylinositol and glutamatergic metabolism in the anterior cingulate cortex of children and adolescents with attention deficit hyperactivity disorder (ADHD) alone, children with ADHD plus bipolar disorder, and children with no axis I diagnosis.Method-Proton spectra were acquired from a 4.8-ml voxel placed in the anterior cingulate cortex of 30 subjects who were 6 to 13 years old. Fifteen subjects had ADHD and no comorbid disorder, eight had ADHD plus bipola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 19 publications
1
49
0
1
Order By: Relevance
“…[32][33][34] Glutamate is a very important excitatory neurotransmitter in the cortico-striato-cerebellar circuit. 35 MRS studies in humans show that 70%-80% of glucose consumption is used to feed the cycle of glutamate in the resting brain.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] Glutamate is a very important excitatory neurotransmitter in the cortico-striato-cerebellar circuit. 35 MRS studies in humans show that 70%-80% of glucose consumption is used to feed the cycle of glutamate in the resting brain.…”
Section: Discussionmentioning
confidence: 99%
“…Brain regions that define the frontal-striatal-cerebellar circuit known to be dysfunctional in ADHD [33][34][35][36] were targeted. To obtain measures of metabolic brain activity using 1 H-MRS, T2-weighted high resolution anatomic images were obtained in the axial plane (TE = 103 ms, TR = 5910 ms, 3 mm slice thickness and 5:27 min:s imaging time).…”
Section: Expression Of Lphn3 In Human Brainmentioning
confidence: 99%
“…Phenomenologic, genetic, family, neuroimaging, neuropsychological and treatment studies revealed that BPD and ADHD have both common and distinct characteristics (Singh et al 2006;Moore et al 2006;Mattis et al 2010). Neuroimaging studies suggested general changes in pre-frontal areas in both disorders, BD and ADHD (Zepf 2009); however, there were primary differences between the two patient groups in the areas of interference control, working memory, planning, cognitive flexibility and fluency (Walshaw et al 2010).…”
Section: Bipolar Disorder (Bd)mentioning
confidence: 99%